DIGITAL FINANCIAL MANAGEMENT MODEL TO ACCELERATE THE TRANSITION TO A GREEN ECONOMY IN THE ENVIRONMENTALLY FRIENDLY TRANSPORTATION SECTOR - Amelia Puspa Tamara; Riky Sambora (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Digital transformation in the financial sector has become a major driver of operational efficiency, transparency, and accelerated decision-making across various industries. At the same time, global demands for the implementation of a green economy are pushing the transportation sector to shift to environmentally friendly business models that require fast and accountable financing support. This study aims to develop a conceptual model that links digital financial management with the acceleration of the green economy transition in the transportation sector. This study uses a qualitative approach based on literature review with theoretical analysis of Scopus-indexed international journals from 2015 to 2024. The results show that digital finance serves as a strategic catalyst for improving efficiency, sustainability reporting, and financing green transportation projects, thereby forming the basis of a digital financial management model for green economic transition.